The accuracy of magnetic resonance cholangiopancreatography in the diagnosis of biliary atresia in preterm infants with cholestasis - Wei-Che Chen; Hsiao-Yu Lo; Yi-Shan Tsai; Yao-Jong Yang (Pediatrics and Neonatology)
Background: Magnetic resonance cholangiopancreatography (MRCP) is a useful and non-invasive method to diagnose biliary atresia (BA) in term infants, however few studies have investigated its use in preterm infants. This study aimed to evaluate the accuracy of MRCP in the diagnosis of BA in preterm infants with cholestasis. Methods: Infants aged less than 6 months who received MRCP for cholestasis at a tertiary medical center were enrolled from 2011 to 2020. Demographic and laboratory data were retrospectively obtained. One pediatric radiologist reviewed the MRCP images. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of MRCP to diagnose BA based on surgical proof or at least 6 months of follow-up were assessed. Results: A total of 80 infants (36 preterm and 44 term) were analyzed. The mean post-chronological age was 1.8 months, and the female-to-male ratio was 0.78. Six (16.7%) preterm and 16 (36.4%) term infants were confirmed to have BA. BA was obscured by a choledochal cyst preoperatively in two term infants. In the preterm infants, the sensitivity, specificity, PPV, NPV, and accuracy of MRCP to diagnose BA were 100%, 77%, 46%, 100%, and 81%, respectively, compared to 81%, 86%, 76%, 89%, and 84% in the term infants. Using MRCP to differentiate BA from other cholestasis in the preterm infants had superior sensitivity (100% vs. 81%) and NPV (100% vs. 89%), and lower specificity (77% vs. 86%) and PPV (46% vs. 76%) than in the term infants. Conclusions: Negative MRCP findings can be used to exclude BA in preterm infants with cholestasis based on a favorable NPV.